The Implementation of Lymphoma Exercises to Reduce Pain and Improve Sleep Quality Using the Theory of Planned Behavior Approach - Wibawa, Shinta Restu; Waluyo, Agung; Nuraini, Tuti (Alta Dharma Publisher, 2025)
Background: Patients with lymphoma often experience various signs and symptoms that can significantly affect their quality of life. Pain and poor sleep quality are two main symptoms commonly experienced by lymphoma patients. The combination of pain and sleep disturbance can negatively impact patients' energy, mood, and ability to perform daily activities, thus requiring appropriate attention and management in the care of lymphoma patients. Objective: This study aims to apply Evidence Based Nursing Practice: Lymphoma Exercises in nursing care for patients with lymphoma using the Theory of Planned Behaviour approach. Method: This approach emphasizes the importance of attitudes, subjective norms, and perceived behavioral control in shaping nursing diagnoses. This framework can enhance understanding and improve patient care. The research method used is a quantitative experiment without a control group. Respondents completed questionnaires to measure pain using the Numerical Rating Scale (NRS), and to measure sleep quality using the Pittsburgh Sleep Quality Index (PSQI). Result: The results show that the intervention had a substantial positive impact on pain and sleep patterns of lymphoma patients. Recommendation: The reduction in pain and improvement in sleep quality can be explained through several potential mechanisms